Trends in Utilization of Total and Unicompartmental Knee Arthroplasty in the United States - Kahlenberg, Cynthia A.; Richardson, Shawn S.; Gruskay, Jordan A.; Cross, Michael B. (The Journal of Knee Surgery, 2020)
Total knee replacement (TKR) and unicompartmental knee replacement (UKR) are successful procedures for patients with knee arthritis. While strict criteria were proposed early on for UKR, some surgeons have expanded these indications to include younger and heavier patients. The purpose of this study is to analyze trends in usage of TKR and UKR in the United States. This retrospective study analyzed an insurance administrative dataset. Patients who underwent primary TKR and UKR were identified via current procedural terminology codes. Information on incidence, obesity, use of computer navigation, and surgical setting were collected. We analyzed 7,194 UKRs and 128,849 TKRs performed from 2007 to 2016. Prevalence of obesity in both groups increased over the study period. Utilization of computer navigation increased for UKR but declined for TKR. The rate of outpatient procedures significantly increased for UKR but remained constant for TKR. Both TKR and UKR are being performed at increasing rates and on heavier patients. The use of computer navigation and outpatient surgical setting is increasing for UKR but not for TKR. Knowledge of these trends is important for surgeons and policy-makers to help inform surgical indications and resource allocation.
Keywords: total knee arthroplasty; unicompartmental knee arthroplasty; trends; utilization